Hubungan Terapi rtPA Dengan Perbaikan Outcome Motorik Pasien Stroke Iskemik Pada Masa Pandemi COVID-19 di Rumah Sakit Al-Islam Bandung - Adli Giardin; Alya Tursina; Wida Purbaningsih (Bandung Conference Series: Medical Science, 2023)
Abstract. COVID-19 pandemic caused a change in regulations that required all patients entering the emergency department (IGD) to be screened for COVID-19. This causes a prolongation of the door to needle time in the rtPA management of ischemic stroke patients. This prolongation of treatment time can affect motor outcomes in patients. The purpose of this study was to analyze differences in door to needle in the management of rtPA ischemic stroke patients in the period before and during the COVID-19 pandemic on motor outcomes at Al-Islam Hospital Bandung. This study was an analytic observational study with a retrospective cohort design. Subjects in this study amounted to 41 patient taken by total sampling. Door to needle secondary data and patient motor outcomes were taken directly from the patient's medical record at Al-Islam Hospital Bandung. Processing of research data was carried out in a computerized manner including univariate and bivariate analysis using the Mann Whitney U test. The study showed that before the pandemic the motor outcome in patients had improved (76%) while during the pandemic the motor outcome in patients had improved (75%) and a value of p = 0.101 was obtained. It was concluded that there was no difference in door to needle administration of rtPA on motor outcomes before and during the COVID-19 pandemic. This is influenced by regulations, rtPA management criteria, and health risk factor. Keywords: Door to Needle, Outcome motoric, rtPA, Stroke iskemic Abstrak. Pandemi COVID-19 menyebabkan perubahan regulasi yang mewajibkan semua pasien yang masuk instalasi gawat darurat (IGD) wajib melakukan skrining COVID-19. Hal ini menyebabkan terjadinya pemanjangan waktu door to needle pada penatalaksanaan rtPA pasien stroke iskemik. Pemanjangan waktu penatalaksanaan ini dapat mempengaruhi outcome motorik pada pasien. Tujuan penelitian ini yaitu untuk menganalisis pengaruh pandemi COVID-19 terhadap door to needle dan outcome motorik pada penatalaksanaan rtPA pasien stroke iskemik di Rumah Sakit Al-Islam Bandung. Penelitian ini adalah observasional analitik dengan desain penelitian kohort retrospektif. Subjek pada penelitian ini berjumlah 41 pasien yang diambil dengan total sampling. Data sekunder door to needle dan outcome motorik pasien diambil langsung melalui rekam medis pasien di RS Al-Islam Bandung. Pengolahan data penilitian ini menggunakan analisis univariat dan bivariat dengan menggunakan uji Mann Whitney. Penelitian menunjukan pada sebelum pandemi hasil outcome motorik pada pasien mengalami perbaikan (76%) sedangkan pada saat pandemi hasil outcome motorik pada pasien mengalami perbaikan (75%) dan didapatkan nilai p=0,101. Disimpulkan bahwa tidak terdapat perbedaan door to needle pemberian rtPA terhadap outcome motorik sebelum dan selama pandemi COVID-19. Hal ini dipengaruhi oleh regulasi, kriteria penatalaksanaan rtPA, dan faktor risiko kesehatan. Kata Kunci: Door to needle, outcome motorik, rtPA, Stroke iskemik